Distance Learning System in Educational System Instead, and Significance - Ravshanova Umida Baxriddinovna; Fozilov Sherzod Musurmonovich (Zien Journals, 2023)
The article is devoted to the urgent problem of modern education - distance education as a new form of education. The main purpose of the article is to justify and discuss distance education as a new form of education. This article defines the main trends in the development of distance education, shows the differences between distance and traditional education. Analyzes a number of problems faced by teachers and students in distance education
Keywords: education; distance education; traditional education